"With Sincere Reverence": A Christological Perspective for the Interreligious Dialogue Envisioned by Nostra Aetate - Gamberini, SJ, Paolo (Studies in Christian-Jewish Relations, 2011)
Theologians have a particular task to provide discernment when expressing in interreligious dialogue the Christological proclamation that Jesus Christ is "'the way, the truth, and the life,' (Jn 14:6), in whom people may find the fullness of religious life, in whom God has reconciled all things to Himself" (Nostra Aetate, Â§3). Therefore, there is a need to renew the spirit of the Conciliar Declaration Nostra Aetate,, which reminds us that the Catholic Church rejects nothing that is true and holy in the other religions. The Church acknowledges with sincere reverence ("sincera cum observantia") that the other often religions reflect a ray of that Truth which enlightens all people. In this article, I highlight three different moments in which this sincere reverence towards other religions may be realized. The first moment may be called methodological and refers to the Ignatian tradition of the Spiritual Exercises. I develop first of all the praesupponendum (presupposition) as an attitude of being able to listen to the religious experience of the other; then the contemplatio ad amorem (contemplation in attaining love), as awareness and recognition of the action of the Spirit: being able to distinguish the religious experience of God from its theoretical and practical interpretations; finally the magis, the continuing transcending of the religious conscience in reaching out God: Deus semper maior (God is always greater). The second moment of my paper is more theoretical. I deal with the question of Truth within the interreligious dialogue and how God’s ineffable transcendence and otherness have been revealed in this Jesus of Nazareth; "No one has seen God at any time; the only begotten God who is in the bosom of the Father, He has explained Him" (Jn 1:18). The humanity of God, Jesus’ particularity, is not a limitation for interreligious dialogue, but constitutes an adequate perspective for determining the universality of Jesus Christ. The third moment considers the practical dimension of the dialogue. I relate the inner otherness of God (Trinity) with God’s becoming other than himself (Incarnation), showing how the evangelical praxis of the believer, who makes himself everything for everybody, is able in the praxis, more than in theory, to sustain the eschatological tension between the already and not yet that is characteric of interreligious dialogue.